Do we help when the situation of need is abstract? The prosocial ef-fect of the disposition to including the macro-environment in life space - Salgado, Sergio; González-Suhr, Carolina; Oceja, Luis (Anales de Psicología / Annals of Psychology, 2013)
We analyze the prosocial effect of including the macro-environment in life space. Namely, it is proposed that the extent to which people perceive that their life takes place in broader environmental contexts (e.g., the society, the world) will facilitate prosocial behavior when the situation of need is presented in an abstract fashion (e.g., very broad and distant). Two studies were conducted to test this hypothesis. In Study 1, we created and tested an instrument to measure the extent to which the macro-environment is included in life space (EV-macro). In Study 2 was included a manipulation of the kind of the need situation (abstract vs. concrete). Results showed that the EV-macro was related to prosocial behavior when the need was presented in relatively more abstract terms